Validity and reliability of a pediatric patient classification instrument - Ariane Polidoro Dini; Daniela Fernanda dos Santos Alves; Henrique Ceretta Oliveira; Edinêis de Brito Guirardello (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to assess the construct validity and reliability of the Pediatric Patient Classification Instrument.METHODS: correlation study developed at a teaching hospital. The classification involved 227 patients, using the pediatric patient classification instrument. The construct validity was assessed through the factor analysis approach and reliability through internal consistency.RESULTS: the Exploratory Factor Analysis identified three constructs with 67.5% of variance explanation and, in the reliability assessment, the following Cronbach's alpha coefficients were found: 0.92 for the instrument as a whole; 0.88 for the Patient domain; 0.81 for the Family domain; 0.44 for the Therapeutic procedures domain.CONCLUSIONS: the instrument evidenced its construct validity and reliability, and these analyses indicate the feasibility of the instrument. The validation of the Pediatric Patient Classification Instrument still represents a challenge, due to its relevance for a closer look at pediatric nursing care and management. Further research should be considered to explore its dimensionality and content validity.